The Influence of MUI Fatwa Number 83 of 2023 on the Purchase Intention of Israeli Products Among the Muslim Community in Makassar City from the Perspective of Sharia Economic Law - Rafiq Rachman N. L. Lewonamang; Muhammad Shuhufi; Abdul Wahid Haddade (widya balina, 2025)
This study examines the influence of the MUI Fatwa Number 83 of 2023 concerning the Legal Ruling on Supporting the Palestinian Struggle on the purchasing interest in Israeli products among the Muslim community in Makassar City, from the perspective of Islamic economic law. The main issue addressed is the low level of public awareness and understanding of the fatwa, amid challenges in identifying products affiliated with Israel and the dominance of global consumer culture. Using a quantitative method within the framework of Islamic economic law, this research involved 156 respondents selected through purposive sampling and analyzed using a Likert scale questionnaire, validation and reliability tests, and regression techniques. The findings indicate that the MUI Fatwa Number 83 of 2023 has a positive and significant effect on purchasing interest (p = 0.000); however, the positive direction of the effect reveals a contradiction between the substance of the fatwa which calls for a boycott and the community’s consumption behavior, which continues to maintain an interest in Israeli-affiliated products. This condition reflects a weak awareness of Islamic economic law among the Muslim community in Makassar City. These findings underscore the need to strengthen education, socialization, and the provision of Sharia-compliant product alternatives to enhance the fatwa’s implementation. Thus, the study concludes that the effectiveness of the fatwa in influencing consumer behavior remains suboptimal and requires ongoing strategic support so that the principles of maslahah, hisbah, and Islamic consumption ethics can be realized in community economic practices.